2013
DOI: 10.1037/a0027279
|View full text |Cite
|
Sign up to set email alerts
|

Cross-generational effects of discrimination among immigrant mothers: Perceived discrimination predicts child's healthcare visits for illness.

Abstract: Objective: This study tested whether an immigrant mother's perception of ethnic and language-based discrimination affects the health of her child (indexed by the child's frequency of sick visits to the doctor, adjusting for well-visits), as a function of her ethnic-group attachment and length of U.S. residency. Method: A community-based sample of 98 immigrant Dominican and Mexican mothers of normally developing 14-month-old children were interviewed. Mothers reported their perceived ethnic and language-based d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Previous studies (Bécares et al 2015;Paradies et al 2015;Harris et al 2015;Tran 2014;Priest et al 2013;Kelly et al 2013;Halim et al 2013;Williams and Mohammed 2009;Pascoe and Smart Richman 2009;Williams et al 2008;Miller and Kaiser 2001;Krieger 2000) show that racial discrimination has a negative effect influence on health outcomes, although mediators and moderators have been noted (Tran 2014;Halim et al 2013;Pascoe and Smart Richman 2009;Noh and Kaspar 2003;Noh et al 1999;Clark et al 1999). One of the few longitudinal studies of immigrant populations and one of the few conducted outside the USA, the UK Millennium Cohort Study of mothers from five ethnic backgrounds, found direct association between experiences of maternal and family racism and children's socioemotional development at age 11 years (Bécares et al 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies (Bécares et al 2015;Paradies et al 2015;Harris et al 2015;Tran 2014;Priest et al 2013;Kelly et al 2013;Halim et al 2013;Williams and Mohammed 2009;Pascoe and Smart Richman 2009;Williams et al 2008;Miller and Kaiser 2001;Krieger 2000) show that racial discrimination has a negative effect influence on health outcomes, although mediators and moderators have been noted (Tran 2014;Halim et al 2013;Pascoe and Smart Richman 2009;Noh and Kaspar 2003;Noh et al 1999;Clark et al 1999). One of the few longitudinal studies of immigrant populations and one of the few conducted outside the USA, the UK Millennium Cohort Study of mothers from five ethnic backgrounds, found direct association between experiences of maternal and family racism and children's socioemotional development at age 11 years (Bécares et al 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Associations between perceived racism and mental health, socioemotional development, or behavioral outcomes have been found in the child and youth literature (Bécares et al 2015;Tran 2014;Priest et al 2013;George et al 2012;Pachter and Coll 2009), with recent studies also examining academic performance (Oxman-Martinez and Choi 2014;Oxman-Martinez et al 2012). Halim et al (2013) found perceived language-based discrimination to be associated with more frequent visits to the doctor for child-related sickness, with ethnic group attachment being a mitigating factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 These social and environmental factors include two relevant stressors facing ethnic-racial minority families in the U.S.: racial-ethnic discrimination and acculturation stress. 49 Discrimination refers to mistreatment based on an individual’s race or ethnicity (e.g., being called a racial-ethnic insult, receiving poor service at a store because of race/ethnicity); acculturation stress refers to stress associated with adapting to different cultures (e.g., learning and communicating in English; adapting to new cultural norms). Whereas research documents substantial costs associated with discrimination and acculturation stress for individuals’ well-being 69 , few studies have examined how the effects of these stressors extend beyond individuals to accumulate within ethnic-racial minority families and, ultimately, impact children’s well-being.…”
mentioning
confidence: 99%
“…20 Although there is less work examining the impact of parents’ acculturation stress on child outcomes, a recent study found that Mexican and Dominican immigrant mothers’ language-based acculturation stress predicted increases in children’s healthcare visits for illness. 4 …”
mentioning
confidence: 99%